2023
DOI: 10.1111/epi.17489
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in cerebral amyloid angiopathy: an observational retrospective study of a large population

Abstract: Objective: Cerebral amyloid angiopathy (CAA) is a major cause of spontaneous intracranial hemorrhage in older adults. Epilepsy represents a possible sequela of the disease. To date, studies on epilepsy in CAA are lacking, and the few data available mainly focus on CAA-related inflammation (CAA-ri), the inflammatory form of the disease. Methods:In this retrospective observational study, we consecutively recruited CAA patients observed over a time span of 10 years, collecting demographic, clinical, and instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
1
6
0
1
Order By: Relevance
“…A recent retrospective study from Tabaee et al reported 33 of 96 (33.3%) patients with CAA were diagnosed with epilepsy during a 13.5‐month follow‐up period [31]. Their report compares to our findings with CAA‐ri and superficial siderosis correlated with a higher incidence of seizures.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A recent retrospective study from Tabaee et al reported 33 of 96 (33.3%) patients with CAA were diagnosed with epilepsy during a 13.5‐month follow‐up period [31]. Their report compares to our findings with CAA‐ri and superficial siderosis correlated with a higher incidence of seizures.…”
Section: Discussionsupporting
confidence: 68%
“…However, the difference was not statistically significant, likely due to the small size of the study cohort and lower incidence of seizures [19]. Our study includes one of the largest cohorts of patients with and without CAA‐ri [31, 45], and supports inflammation associated with CAA as a risk factor for seizures and epilepsy.…”
Section: Discussionmentioning
confidence: 76%
“…In the current study, 4 a cohort of retrospectively identified patients diagnosed with CAA over a 10-year period in a single Center, San Gerardo, in Italy was identified. The diagnosis of CAA was made based on the newly released Boston 2.0 criteria 5 which rely heavily on MRI features suggestive of CAA.…”
Section: Commentarymentioning
confidence: 99%
“…1). Gemäß einer kürzlich publizierten retrospektiven Beobachtungsstudie, erkranken etwa 1/3 aller CAA-Patienten an einer Epilepsie; 80 % haben fokale epileptische Anfälle [18]. Vergleichbar zur pathophysiologischen und MRT-basierten Stadienhaftigkeit der Mikroangiopathie (siehe unten), wird zumindest bei der CAA auch eine Stadienhaftigkeit des Phänotyps diskutiert: kognitive Defizite kennzeichnen wahrscheinlich ein früheres, große Hirnblutungen ein späteres Krankheitsstadium [19].…”
Section: Klinikunclassified